Pengembangan Bahan Ajar Digital Wordwall pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar/Madrasah Ibtidaiyah (Studi Kasus pada Kelas III di SDN Segulung 03, Dagangan, Madiun) - Vigayuli Andari; Meril Qurniawan; Samsudin Samsudin (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Islamic Religious Education (PAI) is an important subject in elementary schools/madrasah ibtidaiyah which has a central role in forming students' noble character and morals. In this digital era, the use of information and communication technology (ICT) in PAI learning has become a necessity to improve the quality and interest in student learning. When choosing teaching materials, you must also pay attention to the surrounding conditions, namely the condition of the students, facilities and infrastructure, etc. The low interest and motivation of students towards PAI subjects has inspired the author to try to innovate new learning media, namely through the Wordwall Platform application which provides various interesting features that can arouse students' attention, awareness and motivation to refocus on the material so that the main goal of education is achieved. namely being able to transfer knowledge to students.